DEVELOPMENT OF VACCINE TRACKING APPLICATION USING AGILE METHODOLOGY - Tegar Arifin Prasetyo (Lambung Mangkurat University, 2022)
Covid-19 is an infectious disease that has plagued the world since the end of 2019 until now. In Indonesia, the Covid-19 case is quite large, so the government requires everyone to get the vaccine. However, the implementation of the vaccine has not been implemented properly. By taking advantage of the current times, a web-based application was built that can track the circulation of vaccines and contain information about the authenticity of vaccines. The development of this application uses an Agile methodology that focuses on the Extreme Programming (XP) model. Extreme Programming (XP) is a method that can simplify several stages of software development. The results of testing conducted by Blackbox testing show that all existing system feature or functionality have run as expected.Keywords: Agile, Covid-19, Extreme Programming, Web-based Appliaction, and Vaccine. Covid-19 merupakan penyakit menular yang menyebar di seluruh dunia sejak akhir tahun 2019 hingga sekarang. Di Indonesia kasus Covid-19 cukup besar, sehingga pemerintah mewajibkan semua orang mendapatkan vaksin. Namun, implementasi vaksin tersebut belum dilaksanakan dengan baik. Dengan memanfaatkan perkembangan zaman, kami membangun sebuah aplikasi berbasis web yang dapat melacak peredaran vaksin dan memuat informasi tentang keaslian data vaksin. Pengembangan aplikasi ini menggunakan metodologi Agile yang berfokus pada model Extreme Programming (XP). Extreme Programming (XP) merupakan sebuah metode yang dapat menyederhanakan beberapa tahap pengembangan perangkat lunak. Hasil pengujian yang dilakukan dengan pengujian Blackbox menunjukkan bahwa semua fitur atau fungsionalitas sistem yang ada telah berjalan sesuai dengan yang diharapkan.Kata kunci: Agile, Covid-19, Extreme Programming, Aplikasi Berbasis Web, dan Vaksin